Taxonomic and Trophic Groups Mediate Latitudinal Variation in Saproxylic Beetle Species Richness and Body Size Across Western Palaearctic Oak Forests - M. Franzen; N. Jansson; M. Avci; A. Brin; H. Brustel; J. Budka; J. Buse; G. Carpaneto; S. Chiari; L. Cizek; M. Coskun; J. Dagley; et al. (Ecology and Evolution)
ABSTRACT We examined latitudinal gradients in species richness and body size of saproxylic beetles across 28 veteran oak forest sites spanning from Israel to Norway. Focusing on 425 species from 11 taxonomic families and five trophic groups, we tested three hypotheses to elucidate: (i) family‐specific richness responses to latitude, (ii) trophic mediation of richness patterns, (iii) whether body size follows Bergmann‐like clines. We found significant family‐level variations in richness–latitude relationships. These non‐uniform patterns highlight the importance of taxonomic resolution in capturing macroecological diversity gradients. Body size analyses revealed significant latitude associations, indicating that both phylogenetic constraints and trophic group modulate latitudinal size patterns among saproxylic beetles. Taken together, our findings emphasize that macroecological patterns in saproxylic beetles are shaped by a synthesis of phylogenetic history and functional traits. Conservation strategies should, therefore, account for family‐level and trophic‐group heterogeneity, particularly as climate warming and shifting resource distributions may differentially affect lineages with distinct thermoregulatory and life‐history constraints. These results underscore the need for taxon‐specific approaches when predicting and managing biodiversity in changing oak forest ecosystems.